Climatic impacts on mortality in pre-industrial Sweden - T. T. Chen; T. T. Chen; R. Edvinsson; K. Modig; H. W. Linderholm; F. C. Ljungqvist; F. C. Ljungqvist; F. C. Ljungqvist (Climate of the Past)
Climate variability and change, as well as extreme weather events, have notable impacts on human health and mortality. In historical times, the effect of climate on health and mortality was stronger than today, owing to factors such as poor housing and healthcare, along with the nutrition status that was meditated through climatic impacts on food production. Despite this, climatic impacts on mortality in the past remain poorly understood. This study aims to improve the understanding of climate effects on mortality using annual mortality records and meteorological data from Sweden between 1749 and 1859. The analysis includes the entire population, as well as subgroups based on sex and age. A statistically significant negative correlation was found between late winter and spring temperatures and mortality (i.e. lower temperatures equal higher mortality, and vice versa). We demonstrate that colder late winter and spring seasons were linked to higher mortality levels, not only for the same year but also for the following year. Conversely, no statistically significant associations were observed between summer or autumn temperatures and mortality, and only weak associations existed with hydroclimate. The impact of late winter and spring season temperature on mortality was most pronounced for the same year in southern Sweden and during the 19th century but stronger for the following year in central Sweden and during the 18th century. These findings call for further research, especially with respect to investigating specific diseases and additional factors contributing to the observed increase in mortality following cold late winter and spring seasons in Sweden during the late pre-industrial period.